Progressive multifocal leukoencephalopathy with immune reconstitution inflammatory syndrome following treatment for granulomatosis with polyangiitis. Issue 3 (May 2018) - Sasaki, Fuyuko; Oyama, Genko; Fujimaki, Motoki; Yokoyama, Kazumasa; Ogasawara, Michihiro; Nakamichi, Kazuo; Saijo, Masayuki; Takasaki, Yoshinari; Hattori, Nobutaka
Abstract: A 56‐year‐old man with granulomatosis with polyangiitis (GPA) developed progressive multifocal leukoencephalopathy (PML) after a combined immune therapy with methotrexate and prednisolone. Despite negative conversion of JC virus after cessation of methotrexate treatment and tapering of prednisone, he developed amnestic aphasia, left hemispatial neglect, and left hemiplegia, which was confirmed as immune reconstitution inflammatory syndrome (IRIS) based on a rapid expansion of the lesions bilaterally with marginal gadolinium enhancement on brain magnetic resonance imaging. This case suggests that it may be important to be aware of possibility of IRIS, in cases of worsening neurological symptoms despite discontinuation of immunosuppressive treatments for GPA with PML.